KRIMINALISASI PEKERJA SEKS KOMERSIAL MELALUI ONLINE (Putusan PN SLEMAN Nomor 564/Pid.Sus/2020/PN Smn) - Widya Pradana, Dimas; Jadidah, Fikrotul (CV. Era Digital Nusantara, 2023)
The rampant practice of prostitution in Indonesia needs to get serious attention considering that so far the practice of prostitution has not have a clear rule of law. So far, positive law in Indonesia only provides punishment for service providers (pimps) only. Meanwhile, commercial sex workers and service users cannot be ensnared by law. The impact of this causes the practice of prostitution to continue to thrive among the community. The research method that the author uses is the normative juridical method, meaning that the data used consists of primary, secondary, and tertiary legal materials. As for the results of the study,that the criminalization of commercial sex workers through online according to positive law in Indonesia by referring to the rules regarding online prostitution outside the Criminal Code is found in Article 2 paragraph (1) of Law no. 21 of 2007 concerning the Crime of Trafficking in Persons, Article 30, Article 33, Article 35 of Law No. 44 of 2008 concerning Pornography, and Article 27 of the ITE Law, but absolutely the commercial sex workers can be held criminally liable using the ITE Law.